EFEK PENURUNAN KEKUATAN GENGGAMAN TANGAN TERHADAP FUNGSI KOGNITIF DAN KESEIMBANGAN PADA LANJUT USIA - Yvonne Suzy Handajani,1 Yuda Turana, 1,2 Nelly Tina Widjaja1 (NEURONA, 2016)
INTRODUCTION THE ABILITY TO GRIP IS ONE OF THE MOST IMPORTANT FUNCTIONS OF THE HAND HAND GRIP STRENGTH CAN BE USED TO REFLECT OVERALL MUSCULAR STRENGTH PREVIOUS STUDY SHOWED THAT MUSCULAR STRENGTH IS ASSOCIATED WITH COGNITIVE FUNCTION AND BALANCE DISTURBANCE IN ELDERLY PEOPLE